1988
DOI: 10.3109/02844318809097935
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation Rate in Osseointegrated Titanium Implants:Influence of Locally Applied Haemostasis, Peripheral Blood, Autologous Bone Marrow and Fibrin Adhesive System (FAS)

Abstract: The influence of local application of haemostasis, peripheral blood, autologous bone marrow and Fibrin Adhesive System (FAS) on bone formation rate in osseointegrated titanium implants, were studied. The Bone Harvest Chamber (BHC) implant utilized has a penetrating canal, enabling osseous ingrowth in situ. After integration of one implant into the cortex of the proximal tibial metaphysis of a rabbit, newly formed bone was harvested in repetitive three-week periods. The specimens were quantified by microradiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
6
1
1
Order By: Relevance
“…For larger constructs, this would facilitate the complete fill of the defect area, and increased adaptation on the defect walls, as well as offer early stability of the graft after placement. The present results of enhanced bone repair are in contrast with the results of studies in which other products, such as fibrin glue or adhesive 44–46 or osteocalcein/osteonectin 47 used to form a moldable grafting material impaired bone formation.…”
Section: Discussioncontrasting
confidence: 99%
“…For larger constructs, this would facilitate the complete fill of the defect area, and increased adaptation on the defect walls, as well as offer early stability of the graft after placement. The present results of enhanced bone repair are in contrast with the results of studies in which other products, such as fibrin glue or adhesive 44–46 or osteocalcein/osteonectin 47 used to form a moldable grafting material impaired bone formation.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors concluded that the “fibrin sealant did not alter blood flow or new bone formation, but a tendency to diminished new bone formation was found in some grafts”. Kalebo et al (1988) inserted bone harvest chamber (BHC) implants in the proximal tibial metaphysis of rabbits to study the effect of autologous bone marrow and a Fibrin Adhesive System on new bone formation. Examination of the retrieved specimens by microradiographic‐videodensitometric methods and histologic analysis showed that the pretreatment with FAS impaired bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Kälebo et al. considered the marginal cell layer of the interface to be the most important stimulator of bone regeneration. A dense peri‐implant lamellar bone with parallel structured elements was observed under loading conditions.…”
Section: Functional Loading Effects On the Cellsmentioning
confidence: 99%